Perbandingan Kuat Tekan Benda Uji Beton Geopolimer Dalam Skala Laboratorium Menggunakan Bahan Prekursor Yang Berbeda - Sundari, Komang Nelly; Supriyadi, Supriyadi; Siagian, Arifin; Suradharmika, IGA (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2022)
This study aimed to compare the compressive strength of various concrete brick compositions made from geopolymers using different clay precursors, including Pejaten clay (PJT), Darmasaba clay (DSB), Waste Tile clay (LG), and dam sediment clay (DAM). Laboratory tests were carried out after 7 days of curing, and the results showed that PJT was the most suitable precursor material for producing geopolymer-based concrete formulas that meet the requirements for solid brick concrete quality class I, with an average compressive strength of 119,926 kg/cm2. The average value of SNI requirements is at least 100 kg/cm2 based on SNI 03-0349-1989 for physical requirement quality standart of concrete bricks. DSB had a compressive strength of 88,808 kg/cm2 and was classified as class II, followed by LG with a compressive strength of 76,366 kg/cm2 and DAM with an average compressive strength of 70.71 kg/cm2, both of which belong to class II. These findings provide valuable insights into the use of different clay precursors for the production of high-quality concrete bricks.